Norepinephrine Transporter is Involved in Down-Regulation of β1-Adrenergic Receptors Caused by Adjuvant Arthritis - John D. Clements; Fakhreddin Jamali (Frontiers Media S.A., 2009)
Purpose. Inflammation in forms of rheumatoid and experimental arthritis cause not only joint pain but also excessive cardiovascular mortality. The condition also reduces response to calcium channel and β-adrenergic (β1-AR) antagonists. For calcium channel inhibitors, the reduced response is shown to be due to the reduced expression of target proteins. Hydroxymethylglutaryl CoA reductase inhibitors (statins) restore response to propranolol and verapamil. We tested the effect of adjuvant arthritis on the norepinephrine (NE) transporter (NET) density since altered sympathetic nervous system innervation has been observed in rheumatoid arthritis. Methods. Male Sprague-Dawley rats were divided into the following groups: Healthy/Placebo, Healthy/Statin, Pre-AA/Placebo, and Pre-AA/Statin (n=7-8/group). On Day 0, to the Pre-AA and Healthy groups, was injected Mycobacterium butyricum or saline, respectively. On Days 4-8, Statin and Placebo groups received either pravastatin (6 mg/kg) or placebo twice daily, respectively. On day 8, heart and blood samples were collected. The density of NET and 1-AR in heart homogenate; NE in plasma and heart and inflammatory mediators (nitrite and interferon-γ) in serum were determined. Results. Inflammation was associated with a significant reduction in both β1-AR and NET density with a positive correlation between the two proteins (r=0.978, p